ANALISIS PENDAPATAN USAHA PETERNAKAN AYAM PETELUR “GOLDEN PANIKI PS” - Ingriet D. R Lumenta; Richard E. M. F. Osak; Vanessa Rambulangi; Stevy P Pangemanan (Jambura Journal of Animal Science, 2022)
This study aimed to analyze the reception, production costs and revenue on the farm Chickens Laying Golden Paniki PS. The research was conducted in the village Tetey Dimembe District of North Minahasa regency in January and February 2021. The determination method using a sample of case study method. This study uses primary data and secondary data. Analysis of the data used in this study using descriptive data analysis. The results of the analysis show that the amount of production costs incurred in the maintenance of laying hens Golden Paniki PS each for fixed costs of Rp.28,676,667 (1.99%) while for variable costs of Rp. 1,440,577,940 (99.05%). The total cost incurred for 3,000 laying hens in one production period is Rp. 1,469,254,607 (100%), the total revenue is Rp. 1,710,288,000/ production period, and the total income of farmers is Rp. 241,033,393/production period. Based on the results of the analysis, it is concluded that the total revenue from the Golden Paniki PS livestock business is Rp. 1,710,288,000/ production period, with a total production cost of Rp.1,469,254,607/ production period, so that the total income earned is Rp. 241,033. 393/production period. Revenue Cost Ratio (R/C Ratio) for laying hens business Golden Paniki PS is obtained with a value of 1,16 or greater than 1, which means this business has a profit so it is feasible to run.